Paths & portals - Yang, Gene Luen (New York, NY : First Second, 2016)
"There's something lurking beneath the surface of Stately Academy, literally. In a secret underground classroom Hopper, Eni, and Josh discover that the campus was once home to the Bee School, an institute where teachers, students, and robots worked together to unravel the mysteries of coding. Hopper and her friends are eager to follow in this tradition and become top-rate coders. But why are Principal Dean and the rugby team suddenly so interested in their extracurricular activities?"
[1]. Get with the program! -- 2. Paths & portals.
Accelerated Reader AR
Keywords: Gifted children -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Computer programming -- Comic books, strips, etc; Cartoons and comics; Computer programming -- Cartoons and comics; Gifted children -- Fiction; Schools -- Fiction; Comic books, strips, etc; Computer programming -- Fiction; Graphic novels; Mystery fiction; Gifted children -- Comic books, strips, etc; Computer programming -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Graphic novels; Comics (Graphic works)